Association of CSF orexin-A levels and nocturnal sleep stability in patients with hypersomnolence. (24th November 2020) - Barateau, Lucie; Lopez, Régis; Chenini, Sofiene; Rassu, Anna-Laura; Scholz, Sabine; Lotierzo, Manuela; Cristol, Jean-Paul; Jaussent, Isabelle; Dauvilliers, Yves
Abstract : Objective: To evaluate the associations between CSF orexin-A (ORX) levels and markers of nocturnal sleep stability, assessed by polysomnography. Methods: Nocturnal polysomnography data and ORX levels of 300 drug-free participants (55% men, 29.9±15.5 years, ORX level 155.1±153.7 pg/mL) with hypersomnolence were collected. Several markers of nocturnal sleep stability were analyzed: sleep and wake bouts and sleep/wake transitions. Groups were categorized according to ORX levels, in 2 categories (deficient ⩽110; >110), in tertiles (⩽26, 26–254, >254), and compared using logistic regression models. Results were adjusted for age, sex, and body mass index. Results: We found higher number of wake bouts (43 vs 25, p < 0.0001), sleep bouts (43 vs 25.5, p < 0.0001), and index of sleep bouts/hour of sleep time, but lower index of wake bouts/hour of wake time (41.4 vs 50.6, p < 0.0001), in patients with ORX deficiency. The percentage of wake bouts <30 seconds was lower (51.3% vs 60.8%, p < 0.001) and of wake bouts ≥1 minutes 30 seconds higher (7.7% vs 6.7%, p = 0.02) when ORX deficient. The percentage of sleep bouts ⩽14 minutes was higher (2–5 minutes: 23.7% vs 16.1%, p < 0.0001), and of long sleep bouts lower (>32 minutes 30 seconds: 7.3% vs 18.3%, p < 0.0001), when ORX deficient. These findings were confirmed when groups were categorized according to ORX tertiles, with a dose–response effect of ORX levels in post hoc comparisons, and in adjusted models. Interpretation: This study shows an association between ORX levels and nocturnal sleep stabilization in patients with hypersomnolence. Sleep and wake bouts are reliable markers of nighttime sleep stability that correlate with CSF ORX levels in a dose-dependent manner.